MATHEMATICS TEXTBOOK ATTRIBUTES AS PREDICTOR OF STUDENTS’ ATTITUDE TO MATHEMATICS - Sunday, Afolabi Samson; Adebowale, Animasahun Isaac (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿The textbook is a pivotal learning material the students cannot do without and it serves as an instructional guide for the teachers. The features of the textbook can affect the interest of the learners positively or negatively and consequently, his attitude. This study is a descriptive survey which considered the correlation of four textbook features (independent variables) with the attitude of students to mathematics (dependent variable). Two validated instruments (Students’ Attitude to Mathematics, r = .72 and Mathematics Textbook Rating Scale, r = .76) were used to collect data from 2,490 students and 117 mathematics teachers respectively. Multistage sampling was used to collect data from the respondents. The findings revealed that there is a positive multiple correlation of the textbook features and students’ attitude to mathematics. The textbook features accounted for 2.8% of variation of students’ attitude to mathematics. The variables do not have composite or any relative significant contributions to students’ attitude to mathematics. The relationship between features of mathematics textbooks and students’ attitude to mathematics is indicative of the need for stakeholders in mathematics textbooks to rethink the type of textbook that can impact positive attitude of students to mathematics.